Policy and Economics of Managed Aquifer Recharge and Water Banking (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
We are pleased to present these 12 papers, all of which were subject to peer review by at least two reviewers. They show the range of economic and policy considerations relevant to the development and implementation of MAR programs. Several papers show novel techniques that can be used to select MAR locations. The importance and economic viability of MAR to semi-arid to arid environments is evident from the use of MAR in both developed and developing regions. Papers demonstrate how MAR can be utilized to meet municipal and agricultural water demands in water-scarce regions, as well as assist in the reuse of wastewater. Some studies explain how stakeholder engagement, ranging from consideration of alternatives to monitoring, and multi-disciplinary analyses to support decision-making are of high value to development and implementation of MAR programs. There is growing recognition of the importance of groundwater and aquifer health to meeting future water needs, as well as the crucial role for strong institutional and governance frameworks for water resources management. The approaches discussed in this collection of papers, along with the complementary and necessary hydrologic and geologic analyses, provide important inputs to water resource managers. We thank the authors for contributing to increased understanding of MAR as a component of sound water management. Sharon B. Megdal and Peter Dillon Guest Editors